2019
DOI: 10.1016/j.lindif.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

How learning time mediates the impact of university Scholars' learning goals on professional learning in research and teaching

Abstract: Empirical investigations of university scholars' learning goals are important to foster high-quality teaching and research. A well-established tenet in achievement goal research is that learning goals elicit actual learning. However, few studies have investigated the mechanisms behind this association. In this study, we propose that learning time links learning goals (i.e., the goal to enhance one's own competences) to learning outcomes in both contexts, research and teaching. In a prospective correlational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 41 publications
(46 reference statements)
6
43
0
Order By: Relevance
“…The structure and usefulness of the above-mentioned achievement goals, as well as their relevance for explaining individual differences in achievement-related experiences and behaviors, has been confirmed in the population of higher education teachers (e.g., Daumiller, Bieg et al, 2020;Daumiller et al, 2019;Daumiller & Dresel 2020a;Daumiller & Dresel, 2020b;Hein et al, 2019;Janke et al, 2019;Rinas et al, 2020). This line of faculty motivation research has largely relied on the overview model developed by Daumiller et al (2019), which has been found to be suitable for characterizing higher education teachers' achievement goals.…”
Section: An Achievement Goal Approach To Higher Education Teachers' Mmentioning
confidence: 96%
“…The structure and usefulness of the above-mentioned achievement goals, as well as their relevance for explaining individual differences in achievement-related experiences and behaviors, has been confirmed in the population of higher education teachers (e.g., Daumiller, Bieg et al, 2020;Daumiller et al, 2019;Daumiller & Dresel 2020a;Daumiller & Dresel, 2020b;Hein et al, 2019;Janke et al, 2019;Rinas et al, 2020). This line of faculty motivation research has largely relied on the overview model developed by Daumiller et al (2019), which has been found to be suitable for characterizing higher education teachers' achievement goals.…”
Section: An Achievement Goal Approach To Higher Education Teachers' Mmentioning
confidence: 96%
“…Within this, established goal classes from prior frameworks and research were integrated into a comprehensive model suitable for characterizing the full scope of university instructors’ achievement goals (see Daumiller et al, 2019b , for details). Based on this model and the respective scale, a series of studies have been conducted and have proven their suitability for assessing university instructors’ achievement goals as well as their relevance for explaining differences in their experiences and behaviors (e.g., Daumiller et al, 2019a , 2020b ; Hein et al, 2019 ; Janke et al, 2019b ; Daumiller and Dresel, 2020a , b ). We therefore also adopted this achievement goal model in the present study given prior empirical evidence and its theoretical fittingness.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the considerations presented above, we expected substantial differences between instructors in their attention, and that these are related to instructors' achievement goals prior to course participation. Building on the aforementioned findings of previous research (e.g., Daumiller et al, 2016;Hein et al, 2019;Hurtz and Williams, 2009;Nitsche et al, 2013a;Nitsche et al, 2013b;Payne et al, 2007), we hypothesized that learning approach goals are positively associated with attention and performance approach, performance avoidance, relational, and work avoidance goals are negatively associated with attention.…”
Section: Research Questions and Hypothesesmentioning
confidence: 93%
“…Strong learning approach goals have been shown to be associated with increased participation in further education courses (Hurtz and Williams, 2009;Nitsche et al, 2013a;Nitsche et al, 2013b), university instructors' planned participation in further education and their attitudes thereto (Diethert et al, 2015), university instructors' attitudes towards help seeking (Daumiller et al, 2019), their learning time (Hein et al, 2019), their own as well as their students' learning gains (Daumiller et al, 2016;Hein et al, 2019), and their selfreported learning effort, intensity, risk-taking, elaboration, implementation, and persistence in professional training courses (Daumiller et al, 2020a).…”
Section: Relevance Of Achievement Goals For Differences In University Instructors' Professional Learningmentioning
confidence: 99%